Rescue Strategic Plan Based on Investment Analysis & Financial Concepts, for A Property Project (Case Study: Anaheim Villa Project, Lake Buyan,Singaraja, Bali) - Amelia, Anggrina; Siahaan, Uke MMP (The Indonesian Journal of Business Administration, 2013)
The topic of this final project is how to save Anaheim Villa from bank foreclosures. The investor want to acquire Anaheim Villa in order to continue to operate and improve the income of this Villa, with acquired 80% of the assets of Anaheim Villa and renamed the Anaheim Villa into Brouillard Bali and optimize the land of these Villas. This cooperation is assessed as the most excellent decision for owners of this Villa, this is caused by the owner can be freed from debt to the bank, and can earn passive income by 20% from Brouillard. Business solutions in the estimate by Brouillard Bali are sell with time-sharing method, This method give management a high return. The implementation of sell with time-sharing villa is sell the luxury new unit to the buyer and also manage the villa rent. This solution give the high NPV and IRR number to the investor. Keywords: Business Property, Time-Sharing, NPV, IRR.